Impact of Treatment Adherence Intervention on a Social Skills Program Targeting Criticism Behaviours - Piccinin, Serge; McCarrey, Michael; Welburn, Ken; Chislett, Lise; Bourgon, Guy; Jacques-Locmelis, Wendy (Canadian Journal of Counselling and Psychotherapy, 1992)
The present study investigates the effect of a cognitive-behaviollral treatment adherence intervention in the course of a criticism skills group training program. Self-monitoring, goal setting, corrective feedback, behavioural contract, procedures to enhance commitment and reinforcement were the techniques used in this intervention. Eighty-six 23-year-Dld volunteer university participants, 62.2% females who reported they had difficulty giving/receiving criticism, and who had a high fear of negative evaluation, were randomly assigned to the treatment condition with or without the adherence intervention or to a waiting list control condition. We found treatment program attendance increased and percentage dropouts reduced by a factor of approximately one half. People who worked on treatment adherence reported differentially improved cognitive antecedents (reduced criticism concerns) and consequences (higher selfesteem/ self-efficacy) and demonstrated better skills (videotape ratings of trained judges) in giving criticism to others. On the other hand, people in the adherence condition reported no differentially improved affective antecedents (fear of negative evaluation) nor cognitive/ affective consequences (self-esteem/self-efficacy) nor did any demonstrate differentially better skills in the way they received criticism. Our results were interpreted in terms of an optimal arousal/avoidance learning paradigm whereupon people's adherence activities facilitated arousal optimal to greater program attendance and outcome gains in the proactive task of giving but not the more reactive task of receiving criticism.